The Effect of Service Quality, Reputation, and Perceived Price on Purchase Decisions with Customer Satisfaction as an Intervening Variable (Study on Parents of Students at Ciputra School Surabaya) - Widarso Bekti Kumoro; Denpharanto Agung Krisprimandoyo (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2023)
The purpose of this study is to test and analyze the influence of Service Quality, Reputation, and Perceived Price on Purchase Decisions and Customer Satisfaction among parents of Ciputra School Surabaya students, as well as to test and analyze the mediating role of Customer Satisfaction in the influence of Service Quality on Purchase Decision and the power of Reputation on Purchase Decision. Service Quality (X1), Reputation (X2), Perceived Price (X3), Customer Satisfaction (Z), and Purchase Decision (Y) are the variables analyzed in this study. Path analysis (Path Analysis) is a technique for analyzing data that begins with the processing of questionnaire data to analyze respondent characteristics and descriptive statistics on the variables Service Quality X1, Reputation (X2), Perceived Price (X3), Customer Satisfaction (Z), and Purchase Decision (Y)—tools for data analysis utilizing PLS with Smart PLS software. The results of testing the hypotheses indicate that Service Quality, Reputation, and Perceived Price have a positive and statistically significant effect on Purchase Decisions. Service Quality and Reputation have a positive and statistically significant influence on Customer Satisfaction, whereas Perceived Price has no effect. Customer Satisfaction could mediate the impact of Service Quality on Purchase Decisions but could not judge the results of Reputation and Perceived Price on Purchase Decisions. The findings of this study indicate that Service Quality has a significant impact on Purchase Decisions made by parents of Ciputra School Surabaya, necessitating the implementation of a number of strategies by management to ensure the future viability and growth of Ciputra School.